Method for measuring microcosmic residual stress of nickel-based alloy large grains

Through the method of focusing ion beam cutting and micro-zone X-ray diffraction measurement, the problem of low microscopic residual stress measurement accuracy in large grains of nickel-based alloy is solved, and high-precision stress measurement is achieved, reducing measurement errors.

CN119555254APending Publication Date: 2025-03-04WUHAN WUCHUAN MEASUREMENT & TEST
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411697063.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-26
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

The existing stress measurement methods have problems such as low accuracy and complex operation for the measurement of microscopic residual stress in large grains of nickel-based alloys.

Method used

By oriented cutting of the large grains to be measured in the nickel-based alloy using a focused ion beam, forming a micron-scale island, and then measuring the grains before and after cutting using the micro-zone X-ray diffraction method, the deformation of the material is calculated, thereby calculating the microscopic residual stress in the large grains of the nickel-based alloy.

Benefits of technology

Accurate measurement of microscopic residual stress in large grains of nickel-based alloys is achieved, which significantly reduces the error of measurement results compared with the existing methods and can more accurately reflect the actual stress state of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119555254A_ABST
    Figure CN119555254A_ABST
Patent Text Reader

Abstract

The invention provides a method for measuring micro residual stress of nickel-based alloy large grains, which comprises the following steps of: directionally cutting selected nickel-based alloy large grains to be measured by using a focused ion beam, firstly cutting out micron-sized islands, and then measuring the grains before and after cutting by using a micro-area X-ray diffraction method to obtain deformation of a material before and after cutting, so as to obtain the micro residual stress of the nickel-based alloy large grains. Therefore, the microscopic residual stress in the nickel-based alloy large grains can be calculated, the microscopic residual stress in the nickel-based alloy large grains can be accurately measured, and the error of a measurement result is obviously reduced compared with that of an existing method.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of material stress measurement, and in particular to a method for measuring large-grain microscopic residual stress of a nickel-based alloy. Technical Background

[0002] Nickel-based alloys are widely used in key fields such as aerospace, energy, etc. due to their excellent high-temperature strength, oxidation resistance and corrosion resistance. Micro stress first originates from the accumulation of dislocations at grain boundaries and the rebound stress after being subjected to force. Residual stress will inevitably be generated during the processing and use of nickel-based alloys. Residual stress will have an important impact on the performance of the material, such as causing material deformation and reducing fatigue life. Especially in large-grained nickel-based alloys, accurate measurement of micro residual stress is crucial to understanding the performance of the material and optimizing the processing technology.

[0003] In this century, with the need for nanomaterial research and development, there have been breakthroughs in micro-stress determination. The cutting method of focused ion beam can cut out micron-sized islands and measure the deformation of the surrounding materials before and after cutting, similar to the mechanical method to calculate the micro-area stress here. Although it is also a lossy measurement, because the damage is extremely small, it can be set up as a separate category besides lossy and non-destructive methods called minimally invasive methods. This type of measurement area can be reduced to the micron level, but it is impossible to determine the grain orientation and it is difficult to obtain the relationship between micro-stress and grain orientation. The micro-Laue diffraction method uses a condenser to focus the white light X-rays of synchrotron radiation into a beam spot of micron to nanometer scale, scans the sample surface moving in the XY plane point by point, and collects the diffraction signal with a two-dimensional detector to obtain the Laue diffraction spectrum. By measuring the difference between the actual position and the theoretical position of the diffraction peak, the deviatoric strain tensor can be obtained. At this time, the micro-stress obtained is related to the crystal orientation. By using the penetration depth of the X-ray and adjusting the aperture, the micro-stress value below the table can also be obtained. However, the micro-Laue method is only possible with dedicated stations for cyclotron X-rays. So far, there are no more than 10 dedicated stations for cyclotron X-rays in the world, and the Shanghai Light Source only started to build a station this year. Although the units doing micro-stress research are limited by means, the limited test results have a great impact. This is because it was originally believed that very small micro-stresses can reach an order of magnitude close to the yield strength, which is a factor that cannot be ignored in practical applications. In the past, only the role of macroscopic residual stress was considered, which may not reflect objective facts. The existing stress measurement methods have problems such as low accuracy and complex operation for the measurement of micro-residual stress in large grains of nickel-based alloys. Therefore, a new and effective measurement method is needed. Summary of the invention

[0004] The present invention uses a focused ion beam to perform directionally cutting on the selected large grains of nickel-based alloy to be tested, first cutting out micron-sized islands, and then using the micro-area X-ray diffraction method to measure the grains before and after cutting. The deformation of the material before and after cutting can be obtained, thereby calculating the microscopic residual stress in the large grains of the nickel-based alloy.

[0005] In order to achieve the above object, the present invention provides a method for measuring microscopic residual stress of large grains of nickel-based alloy, comprising the following steps:

[0006] S1, using a focused ion beam to perform directional cutting of the selected large grains of nickel-based alloy to be tested;

[0007] S2, cutting the large grains to be tested into micron-sized islands;

[0008] S3, measurement of large grains before and after cutting using micro-area X-ray diffraction;

[0009] S4, calculating the deformation of the material before and after cutting according to the measured data;

[0010] S5, calculate the micro residual stress within the large grains of nickel-based alloy.

[0011] Furthermore, in step S1, when cutting is performed using a focused ion beam, gallium is used as an ion source; the ion energy is generally in the range of 20-30 keV; and the cutting speed is controlled between 20 nanometers per second and 80 nanometers per second.

[0012] For metal materials, gallium ions can usually achieve better cutting effects because they interact more appropriately with metal atoms and can effectively achieve sputtering removal of materials. The ion energy is generally in the range of 20-30keV. Lower energy (such as 5-20keV) is suitable for fine processing and surface finishing of materials, which can reduce the impact on the internal structure of the material; higher energy (such as 30-50keV) can speed up the cutting speed, but may introduce more problems such as lattice damage.

[0013] The cutting speed is usually adjusted between a few nanometers per second and a few microns per second. A slower cutting speed (such as a few nanometers per second) is conducive to obtaining a high-quality cut surface, because it allows the ion beam to have enough time to fully interact with the material, so that the material is removed evenly and the roughness and defects of the cut surface are reduced. However, a too slow cutting speed will lead to a long cutting time, affecting work efficiency.

[0014] On the contrary, a faster cutting speed (such as a few hundred nanometers per second to a few micrometers per second) can improve cutting efficiency, but may cause the quality of the cut surface to deteriorate, resulting in unevenness such as steps, potholes, etc. In the preferred calculation scheme, the cutting speed is controlled between 20 nanometers per second and 80 nanometers per second, which can obtain a high-quality cut surface, reduce the roughness and defects of the cut surface, and at the same time not affect the cutting efficiency.

[0015] Furthermore, before cutting, the sample is ground and polished to make the surface roughness Ra value less than 0.1 μm.

[0016] The surface of the nickel-based alloy sample must be finely ground and polished to achieve extremely high flatness and finish. The surface flatness is required to be at the micron or even submicron level to ensure that the X-rays can be evenly irradiated on the sample surface, reduce the X-ray scattering caused by the uneven surface, make the diffraction peak clearer and sharper, and facilitate accurate measurement of parameters such as the interplanar spacing. The method of polishing after gradual grinding (from coarse sandpaper to fine sandpaper) can be adopted, such as using diamond polishing paste for final polishing to ensure that the surface roughness Ra value is less than 0.1μm.

[0017] Furthermore, the particle size of the micron-sized islands is 1-5 μm, and the thickness of the micron-sized islands is between 20 um and 100 um.

[0018] If the particle size of the micron-sized island is too large, the result will reflect the comprehensive average of the characteristics of different internal regions, which is difficult to accurately reflect the local real situation. At the same time, affected by the surrounding grains and the macroscopic structure of the material, this influence from the surrounding environment may cover up the real characteristics of the large grains themselves, so that the measurement results based on the overall large grains cannot accurately reflect the actual stress state, crystal structure, etc. inside. The particle size of the micron-sized island is 1-5μm. The stress, crystal structure and other characteristics of the material are more consistent locally, and the stress state and crystal structure information of the specific micro-region can be obtained more accurately, avoiding the measurement error caused by the internal inhomogeneity of the large grains. Within this particle size range, the micron-sized island can be relatively isolated from the macroscopic interference environment, so that the measurement results can more truly reflect the original microscopic characteristics of the micron-sized grains themselves, and are not interfered by macroscopic factors such as the orientation of the surrounding grains and the stress distribution. The thickness of the micron-sized island can be between 20 microns and 100 microns, so that the X-rays can penetrate the area of ​​interest more effectively and reduce the interference of the deep structure on the measurement; but if the thickness is too thin, it is impossible to fully obtain the comprehensive information of the thickness direction of the entire sample.

[0019] Further, in step S3, the X-ray uses Cu-Kα ray (wavelength of 0.15406nm) or Mo-Kα ray (wavelength of 0.07107nm); the incident angle and the diffraction angle are in the range of 20°-80°, preferably 40°; and the step size is set between 0.05°-0.1°.

[0020] For nickel-based alloys, Cu-Kα rays (wavelength 0.15406nm) or Mo-Kα rays (wavelength 0.07107nm) can usually be used. Cu-Kα rays are more commonly used in nickel-based alloy measurements because their energy and penetration ability are relatively moderate, and they can interact well with the elements in nickel-based alloys to produce clear diffraction signals. However, if the nickel-based alloy contains more high atomic number elements and has higher requirements for penetration depth, Mo-Kα rays may be more suitable, as their shorter wavelength can enhance penetration ability and reduce the influence of surface layer elements on the measurement;

[0021] Select the appropriate incident angle and diffraction angle according to the crystal structure characteristics of nickel-based alloys. Nickel-based alloys usually have a more complex crystal structure, and generally several possible optimal angle ranges can be determined through theoretical analysis or preliminary experiments. Usually, preliminary screening is carried out in the range of 20°-80°, and then the angle selection is further optimized based on the clarity and resolution of the diffraction peaks obtained from actual measurements, as well as whether it can accurately reflect the changes in the interplanar spacing. For example, for the measurement of specific crystal planes of certain nickel-based alloys, it may be found that the combination of an incident angle and a diffraction angle of about 45° can obtain the clearest diffraction signal that most accurately reflects the stress state.

[0022] At the same time, a balance must be struck between measurement accuracy and measurement efficiency. For materials such as nickel-based alloys that may have complex microstructures and stress distributions, relatively long measurement times and slower scanning speeds are generally required to ensure measurement accuracy. However, the specific value should be determined based on factors such as the diffraction signal intensity of the sample and the stability of the instrument. Usually, the measurement time can be between a few minutes and tens of minutes, and the scanning speed can be between 0.1° / second and 1° / second. For example, if the diffraction signal intensity of the sample is weak, it may be necessary to set the measurement time to more than 30 minutes and the scanning speed to 0.1° / second to ensure that sufficiently clear diffraction information can be accurately obtained.

[0023] When actually changing the measurement angle (such as scanning measurement with a certain angle step), the step size should be set reasonably. For nickel-based alloy measurement, the step size can generally be set between 0.05° and 0.2°. If the step size is too small, it will increase the measurement time and data volume, increase the difficulty of data processing and possible errors; if the step size is too large, some key diffraction information may be missed, resulting in an inaccurate description of the change in crystal plane spacing, which in turn affects the calculation accuracy of parameters such as stress.

[0024] During the measurement process, sufficient intensity is required to ensure sufficient diffraction signal intensity when measuring micro areas, and at the same time, the intensity must be stable to avoid measurement errors caused by intensity fluctuations. For example, a high-power enclosed X-ray tube is used, whose output power is stable and can meet the needs of long-term, high-precision measurements.

[0025] Furthermore, in S3, before cutting the large grains of nickel-based alloy, the micro-area X-ray diffraction method is used to measure the interplanar spacing d0 of specific crystal planes in the large grains; after cutting the large grains, the micro-area X-ray diffraction method is used again to measure the interplanar spacing d1 of the same crystal plane.

[0026] Furthermore, in S4, the relative change in the interplanar spacing is calculated according to the formula ε=d1-d0 / d0, where ε is the deformation of the material.

[0027] Further, in S5, the micro residual stress σ is calculated according to the generalized Hooke's law σ=Eε / (1+V), where E is the elastic modulus of the nickel-based alloy and V is the Poisson's ratio.

[0028] Beneficial effects of the present invention:

[0029] Designed for large grains of nickel-based alloys, it can adapt well to the characteristics of large-grain materials and solve the problem of difficult measurement of micro-residual stress in large grains; by optimizing the cutting conditions of the focused ion beam and the measurement parameters of the micro-area X-ray diffraction method, the cutting accuracy is improved and high-precision X-ray measurement is achieved, so the micro-residual stress in large grains of nickel-based alloys can be accurately measured, and the error of the measurement results is significantly reduced compared with the existing methods; at the same time, for large-grain materials, the anisotropy of the crystal has a significant effect on the residual stress. The micro-area X-ray diffraction method can fully consider the anisotropy of the crystal during the measurement process, and the residual stress state in the large grains can be more accurately determined by measuring and analyzing different crystal plane directions; there are differences in the response of different crystal plane directions to stress. Through comprehensive measurement and analysis, stress results that are more in line with the actual situation can be obtained. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 It is a schematic flow chart of the method for measuring the microscopic residual stress of large grains of nickel-based alloy according to the present invention; DETAILED DESCRIPTION

[0031] To make the technical solutions and advantages of the present invention more clear, the present invention and its beneficial effects will be described in further detail below in conjunction with specific implementation methods and accompanying drawings, but the implementation methods of the present invention are not limited thereto.

[0032] In the present invention, "at least one" means one or more, and "more than one" means two or more. "At least one of the following" or similar expressions refers to any combination of these items, including any combination of single items or plural items. For example, "at least one of a, b, or c", or "at least one of a, b, and c", can all mean: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, c can be single or multiple.

[0033] See also Figure 1 , the technical solution adopted by the present invention is as follows:

[0034] S1, using a focused ion beam to perform directional cutting of the selected large grains of nickel-based alloy to be tested;

[0035] Select a nickel-based alloy sample and identify the large grains to be tested under a microscope; set the parameters of the focused ion beam device, such as setting the ion beam energy to 30keV and the scanning speed to 40nm / s, and perform directional cutting on the selected large grains. The cutting path is pre-planned according to the shape of the large grains and the measurement requirements to ensure the accuracy of the cutting. When using X-rays to measure the sample, the uneven surface of the sample will cause irregular scattering of the X-rays on the surface, making the diffraction peaks wider, weaker, and the peak position shifted. This will make it difficult to accurately determine the interplanar spacing, because a flat surface is essential for obtaining clear and accurate diffraction peaks, and inaccurate interplanar spacing measurements will inevitably affect the calculation accuracy of residual stress. The focused ion beam can selectively cut in a specific micro area of ​​the sample without affecting other surrounding areas, which is very useful for analyzing the local structure inside the material or processing specific phases in multiphase materials.

[0036] S2, cutting the large grains to be tested into micron-sized islands;

[0037] The focused ion beam is continuously controlled to perform the cutting operation until a small island structure with a size of 1-5μm is formed, and the thickness of the micron-sized island is between 20um-100um. The micro-area X-ray diffraction method relies on an X-ray beam that can be focused on a very small area for measurement, and its measurement spot size is usually in the order of microns or even smaller. After the grains are cut into micron size, their size can be better matched with the measurement spot size of the micro-area X-ray diffractometer and the resolution of the instrument. During the cutting process, the cutting situation is observed in real time through an electron microscope to ensure that the shape and size of the island meet the requirements.

[0038] The stress distribution inside large grains may not be uniform. By cutting to form micron-sized islands, the measurement area can be reduced to a more representative micro-area. At the micron scale, the stress state of the material is relatively more uniform and can more accurately reflect the local stress characteristics. For example, in some large grains of nickel-based alloys that have undergone complex processing, there may be local stress differences due to processing heat effects or uneven deformation. Micron-sized islands help to accurately capture these local stresses. At the same time, large grains at the macro scale are often affected by surrounding grains and the overall structure of the material, which can mask the true stress state inside the large grains. After cutting it into micron-sized islands, it can effectively isolate interference factors from the surrounding environment, so that the measurement results can more accurately reflect the microscopic residual stress of the large grains themselves. For example, in polycrystalline materials, the different orientations and stress states of adjacent grains will affect the target large grains, and micron-sized islands can reduce this effect.

[0039] Micro-area X-ray diffraction requires precise measurement of specific tiny areas. The size of the micron-sized island matches the measurement spot size and resolution of the micro-area X-ray diffractometer. This ensures that the measurement beam can be accurately focused on the target area to obtain a clear and accurate diffraction signal. For example, a high-precision micro-area X-ray diffractometer can focus the X-ray beam to an area of ​​a few microns or even smaller, and the micron-sized island just meets the requirements of this measurement technology.

[0040] In the actual measurement process, if the particle size of the micron-sized island is too large, the result will reflect the comprehensive average value of the characteristics of different internal regions, which is difficult to accurately reflect the actual local situation. At the same time, affected by the surrounding grains and the macroscopic structure of the material, this influence from the surrounding environment may mask the true characteristics of the large grains themselves, making the measurement results based on the large grains as a whole unable to accurately reflect the actual stress state, crystal structure, etc. inside. The particle size of the micron-sized island is 1-5μm. The stress, crystal structure and other characteristics of the material are more consistent locally, and the stress state and crystal structure information of the specific micro-region can be obtained more accurately, avoiding the measurement error caused by the internal inhomogeneity of the large grains. Within this particle size range, the micron-sized island can be relatively isolated from the macroscopic interference environment, so that the measurement results can more truly reflect the original microscopic characteristics of the micron-sized grains themselves, and are not affected by macroscopic factors such as the surrounding grain orientation and stress distribution. The thickness of the micron-sized islands can be between 20 and 100 microns, so that X-rays can penetrate the area of ​​interest more effectively and reduce the interference of deep structures on the measurement; but if the thickness is too thin, it is impossible to fully obtain the comprehensive information of the entire sample thickness direction.

[0041] S3, measurement of large grains before and after cutting using micro-area X-ray diffraction;

[0042] In this step, the sample with micron-sized islands is placed on the sample stage of the micro-area X-ray diffractometer, and the position of the sample stage is adjusted to ensure that the islands are within the X-ray irradiation range. The basic principles of X-ray diffraction are introduced below.

[0043] When a beam of X-rays hits a crystal, diffraction occurs. Bragg's law is the basic law of X-ray diffraction, and its expression is nλ=2dsinθ, where n is the diffraction order, λ is the wavelength of the X-rays, d is the interplanar spacing of the crystal, and θ is the incident angle (or diffraction angle) of the X-rays. In micro-area X-ray diffraction measurements, the interplanar spacing can be calculated using the known X-ray wavelength and the measured diffraction angle.

[0044] For nickel-based alloys, Cu-Kα rays (wavelength 0.15406nm) or Mo-Kα rays (wavelength 0.07107nm) can usually be used. Cu-Kα rays are more commonly used in nickel-based alloy measurements because their energy and penetration ability are relatively moderate, and they can interact well with the elements in nickel-based alloys to produce clear diffraction signals. However, if the nickel-based alloy contains more high atomic number elements and has higher requirements for penetration depth, Mo-Kα rays may be more suitable, as their shorter wavelength can enhance penetration ability and reduce the influence of surface layer elements on the measurement;

[0045] Select the appropriate incident angle and diffraction angle according to the crystal structure characteristics of nickel-based alloys. Nickel-based alloys usually have a more complex crystal structure, and generally several possible optimal angle ranges can be determined through theoretical analysis or preliminary experiments. Usually, preliminary screening is carried out in the range of 20°-80°, and then the angle selection is further optimized based on the clarity and resolution of the diffraction peaks obtained from actual measurements, as well as whether it can accurately reflect the changes in the interplanar spacing. For example, for the measurement of specific crystal planes of certain nickel-based alloys, it may be found that the combination of an incident angle and a diffraction angle of about 45° can obtain the clearest diffraction signal that most accurately reflects the stress state.

[0046] At the same time, a balance must be struck between measurement accuracy and measurement efficiency. For materials with complex microstructures and stress distributions such as nickel-based alloys, in order to ensure measurement accuracy, the measurement time usually takes several minutes to several dozen minutes, and the scanning speed is between 0.1° / second and 1° / second. The specific value is determined based on factors such as the sample diffraction signal intensity and instrument stability. If the sample diffraction signal is weak, the measurement time may need to be set to more than 30 minutes, and the scanning speed is 0.1° / second to obtain clear diffraction information.

[0047] In the actual seven, when changing the measurement angle (such as scanning measurement with a certain angle step), the step size should be set reasonably. For nickel-based alloy measurement, the step size can generally be set between 0.05°-0.2°. If the step size is too small, it will increase the measurement time and data volume, increase the difficulty of data processing and possible errors; if the step size is too large, some key diffraction information may be missed, resulting in an inaccurate description of the change in crystal plane spacing, which in turn affects the calculation accuracy of parameters such as stress.

[0048] During the measurement process, sufficient intensity is required to ensure sufficient diffraction signal intensity when measuring micro areas, and at the same time, the intensity must be stable to avoid measurement errors caused by intensity fluctuations. For example, a high-power enclosed X-ray tube is used, whose output power is stable and can meet the needs of long-term, high-precision measurements.

[0049] Measurement before cutting: Before cutting the large grains of nickel-based alloy, the micro-area X-ray diffraction method is used to measure the interplanar spacing d0 of specific crystal planes in the large grains. This step requires precise control of the X-ray incident angle, wavelength and other parameters to ensure the accuracy of the measurement. For example, for a large grain of nickel-based alloy, its typical low-index crystal plane is selected for measurement, and the X-ray wavelength can be selected from common rays (wavelengths), and the interplanar spacing d0 is determined by the Bragg law.

[0050] Measurement after cutting: After cutting the large grains, use the micro-area X-ray diffraction method to measure the interplanar spacing d1 of the same crystal plane again. Since the cutting process may cause changes in the internal stress state of the material, the interplanar spacing will change. Also follow the above measurement method to ensure the consistency of the measurement conditions to accurately obtain the change in interplanar spacing.

[0051] S4, calculating the deformation of the material before and after cutting according to the measured data;

[0052] When residual stress exists inside the material, it will cause strain in the crystal. According to the elastic mechanics theory of the material, the interplanar spacing of the crystal will change under stress. For isotropic materials, the relationship between stress and strain can be described by the generalized Hooke's law. Residual stress will cause the crystal to stretch or compress to varying degrees in different directions, thereby changing the interplanar spacing. On a microscopic scale, this change in interplanar spacing can be measured by X-ray diffraction, and the relative change in interplanar spacing is calculated according to the formula ε = d1-d0 / d0, where ε is the deformation of the material. The strain here reflects the degree of material deformation caused by the cutting operation.

[0053] S5, calculate the micro residual stress within the large grains of nickel-based alloy.

[0054] For nickel-based alloys, it is usually assumed to be an isotropic material (in some cases, if more accurate results are required, the anisotropy of the material can be considered), and the micro-residual stress σ is calculated according to the generalized Hooke's law σ=Eε / (1+V). Where E is the elastic modulus of the nickel-based alloy, and V is the Poisson's ratio. For nickel-based alloys, the elastic modulus is generally in the range of 150-220GPa, and the Poisson's ratio is about 0.3. The specific values ​​can be found in the material manual or more accurate values ​​can be obtained through experimental measurements.

[0055] During the entire measurement process, the accuracy of micro-area X-ray diffraction measurements must be ensured, such as calibrating the instrument, accurately setting the measurement parameters, and taking the average of multiple measurements to reduce measurement errors. For example, the instrument's angle measurement accuracy must reach a high level to prevent errors in the calculation of crystal plane spacing due to inaccurate angle measurement.

[0056] Different nickel-based alloys may have differences in their elastic modulus and Poisson's ratio due to factors such as composition and processing technology. When calculating micro-residual stress, it is necessary to accurately obtain these characteristic parameters of the material under study to ensure the accuracy of stress calculation.

[0057] When selecting micro-area measurement, it should be ensured that the selected micro-area can represent the stress state within the large grains. In view of the possible stress inhomogeneity of large grains, multiple micro-area measurements can be selected and the results can be comprehensively analyzed to obtain more reliable microscopic residual stress data.

[0058] The above are only exemplary embodiments of the present disclosure, and the scope of the present disclosure cannot be limited thereto. That is, any equivalent changes and modifications made according to the teachings of the present disclosure are still within the scope of the present disclosure.

Claims

1. A method for measuring large-grain microscopic residual stress of nickel-based alloy, characterized in that: The steps include: S1, using a focused ion beam to perform directional cutting of the selected large grains of nickel-based alloy to be tested; S2, cutting the large grains to be tested into micron-sized islands; S3, measurement of large grains before and after cutting using micro-area X-ray diffraction; S4, calculating the deformation of the material before and after cutting according to the measured data; S5, calculate the micro residual stress within the large grains of nickel-based alloy.

2. The method for measuring large-grain microscopic residual stress of nickel-based alloy according to claim 1, characterized in that: In step S1, when cutting is performed using a focused ion beam, gallium is used as an ion source; the ion energy is generally in the range of 20-30 keV; and the cutting speed is controlled between 20 nanometers per second and 80 nanometers per second.

3. The method for measuring large-grain microscopic residual stress of nickel-based alloy according to claim 1, characterized in that: Before cutting, the sample is ground and polished to make the surface roughness Ra value less than 0.1μm.

4. The method for measuring large-grain microscopic residual stress of nickel-based alloy according to claim 1, characterized in that: The particle size of the micron-sized islands is 1-5 μm; the thickness of the micron-sized islands is between 20 μm and 100 μm.

5. The method for measuring large-grain microscopic residual stress of nickel-based alloy according to claim 1, characterized in that: In step S3, the X-ray uses Cu-Kα ray (wavelength 0.15406nm) or Mo-Kα ray (wavelength 0.07107nm); the incident angle and diffraction angle are in the range of 20°-80°, preferably 40°; the step size is set between 0.05°-0.1°.

6. The method for measuring large-grain microscopic residual stress of nickel-based alloy according to claim 1, characterized in that: In S3, before cutting the large grains of nickel-based alloy, the micro-area X-ray diffraction method is used to measure the interplanar spacing d0 of specific crystal planes in the large grains; after cutting the large grains, the micro-area X-ray diffraction method is used again to measure the interplanar spacing d1 of the same crystal plane.

7. The method for measuring large-grain microscopic residual stress of nickel-based alloy according to claim 1, characterized in that: In S4, the relative change in the interplanar spacing, ie, the deformation of the material, is calculated according to the formula ε=d1-d0 / d0.

8. The method for measuring large-grain microscopic residual stress of nickel-based alloy according to claim 1, characterized in that: In S5, the micro residual stress σ is calculated according to the generalized Hooke's law σ=Eε / (1+V), where E is the elastic modulus of the nickel-based alloy and V is the Poisson's ratio.